Nodular Hyperplasia of the Liver - Arora, Sudhir (1982)
In recent years a number of cases of focal nodular hyperplasia have been reported, most in young females who use oral contraceptives. The pathophysiologic mechanism has been postulated, but is not well understood. In this case of focal nodular hyperplasia, abnormal findings on angiographic and radionuclide studies suggest the use of these procedures in preoperative diagnosis.